Effectiveness of toothpastes in reducing Streptococcos mutans count in children aged 5 year old - De la Cruz Campos, Silvia Beatriz (2021)
Objective: Determine which of the toothpastes; a toothpaste with 1.5% arginine and 1450 ppm fluoride, one with 10% xylitol and 1450 ppm fluoride and a toothpaste with 1450 ppm fluoride; It is most effective in reducing the saliva count of S. mutans in 5-year-old children. Materials and methods: The sample consisted of forty-five 5-year-old children divided into 3 groups corresponding to each paste to be evaluated, a toothpaste with 1.5% arginine and 1450 ppm of fluoride, one with 10% xylitol and 1450 ppm of fluoride and one with 1450 ppm of fluoride. Counts of CFU of S. mutans were carried out in sowings made on MSB agar, of stimulated saliva samples obtained from the subjects of the sample, before and after two weeks of the use of the paste assigned to each subgroup. Results: The mean S. mutans count before was 727.59 CFU and after it was 103.50. The significance was 0.000 between the count of S. mutans before and after the use of the pastes in the three groups evaluated. A statistically significant difference was found between the 3 groups, finding that the group with the paste with 10% xylitol and 1450 ppm fluoride was more effective than the other two toothpastes. Conclusion: All three toothpastes were shown to be effective in reducing the S. mutans count in saliva in 5-year-old children, however, the toothpaste with 10% xylitol and 1450 ppm fluoride proved to be more efficient than the two other pastes..